2003
DOI: 10.1073/pnas.0535926100
|View full text |Cite
|
Sign up to set email alerts
|

Variable character of O—O and M—O bonding in side-on (η 2 ) 1:1 metal complexes of O 2

Abstract: The structures and the OOO and MOO bonding characters of a series of reported side-on ( 2 ) 1:1 metal complexes of O2 are analyzed by using density functional theory calculations. Comparison of the calculated and experimental systems with respect to OOO bond distance, OOO stretching frequency, and OOO and MOO bond orders provides new insights into subtle influences relevant to O2 activation processes in biology and catalysis. The degree of charge transfer from the generally electronrich metals to the dioxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
321
2
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(374 citation statements)
references
References 41 publications
49
321
2
2
Order By: Relevance
“…4 B and C). This strong interaction leads to a covalently delocalized singlet ground state for the side-on Cu II -superoxo species with no spin polarization (i.e., no net antiparallel spin localization on the Cu II and the superoxide ligand), arguing against an antiferromagnetic exchange-coupled description (or biradical) previously used for the diamagnetism of Cu II -superoxo species (21)(22)(23) (Fig. 4B versus Fig.…”
mentioning
confidence: 82%
“…4 B and C). This strong interaction leads to a covalently delocalized singlet ground state for the side-on Cu II -superoxo species with no spin polarization (i.e., no net antiparallel spin localization on the Cu II and the superoxide ligand), arguing against an antiferromagnetic exchange-coupled description (or biradical) previously used for the diamagnetism of Cu II -superoxo species (21)(22)(23) (Fig. 4B versus Fig.…”
mentioning
confidence: 82%
“…In both of these cases, the resulting compounds with a variety of ligands can have singlet ground states that exhibit substantial biradical character because of the spin separation associated either with two d 9 Cu͑II͒ ions or one such ion and a superoxide radical anion. [40][41][42][43][44][45][46][47][48][49][50][51][52] Wave function theories restricted to a single determinant are poorly suited to the description of such species since singlet biradicals are intrinsically two determinantal. 53,54 Moreover, even when oxidation states more likely to be characterized as closed shell in nature are considered, e.g., ͓LCu͑III͔͒ 2 ͓O͑2−͔͒ 2 , computational studies have found that large contributions from dynamical correlation effects influence relative isomer energetics.…”
Section: Application To Supported Cuo 2 and Cu 2 O 2 Systemsmentioning
confidence: 99%
“…53,54 Moreover, even when oxidation states more likely to be characterized as closed shell in nature are considered, e.g., ͓LCu͑III͔͒ 2 ͓O͑2−͔͒ 2 , computational studies have found that large contributions from dynamical correlation effects influence relative isomer energetics. [40][41][42][47][48][49]51,52 In this section, we apply the RASPT2 method to two problems previously studied in considerable detail using a wide range of theoretical models ͑see Fig. 2͒.…”
Section: Application To Supported Cuo 2 and Cu 2 O 2 Systemsmentioning
confidence: 99%
“…Moreover, covalent character in the Cu-O bonding can lead to electronic structures best viewed as intermediate between pairs of formal oxidation states. 8,11,16,35 Scheme 1 illustrates those cases for which significant structural and spectral data are available. The first case, 1, is an end-on precatalytic complex of O 2 in the Cu B site of peptidylglycine R-hydroxylating monooxygenase (PHM).…”
Section: Introductionmentioning
confidence: 99%